2012
DOI: 10.1002/pssa.201228128
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence characteristics of Sr1−xBaxSi2O2N2:Eu2+ phosphors for white light emitting diodes

Abstract: Sr1−xBaxSi2O2N2:Eu2+ phosphors were synthesized using high temperature solid state reaction. The effect of Ba incorporation on the structural and luminescence characteristics of SrSi2O2N2:Eu2+ phosphors were studied. The phosphors were crystallized in triclinic crystal structure and the cell volume increases monotonically with Ba addition. The PL emission peak wavelength red shifts with Ba up to x = 0.50 beyond which no red shift is observed. The XPS analysis shows that nitrogen is being incorporated into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The dashed line shows, based on points reported by different groups (Refs. 15,17,33,45,39, and this work), that the volume does not vary with Eu substitution. The scatter of the experimental points (especially that for Ce and Yb points added to the figure) can be attributed to differences in technology leading to compositional differences (such as a deviation in N/(N+O) ratio).…”
Section: A Phase Analysis and Rietveld Refinementsupporting
confidence: 63%
See 2 more Smart Citations
“…The dashed line shows, based on points reported by different groups (Refs. 15,17,33,45,39, and this work), that the volume does not vary with Eu substitution. The scatter of the experimental points (especially that for Ce and Yb points added to the figure) can be attributed to differences in technology leading to compositional differences (such as a deviation in N/(N+O) ratio).…”
Section: A Phase Analysis and Rietveld Refinementsupporting
confidence: 63%
“…No systematic studies of α-SrSi 2 O 2 N 2 unit-cell size variation with doping could be found in literature, except that for Ba substitution at Sr sites (a monotonic increase is reported 45 ). Substituting a small amount of Eu 2+ ions at Sr sites is known to have no significant influence on the cell volume; 29 all six lattice parameters differ marginally between the side compounds, as Table II shows.…”
Section: A Phase Analysis and Rietveld Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 5d–4f transitions induce broad emission bands whose positions vary with the local environment of rare-earth ions in the host lattice. Thus, some Eu-doped oxynitrides have recently shown very attractive luminescence properties, such as AlN [25], α - and β -SiAlON [2628], M 2 Si 5 N 8 and MSi 2 O 2 N 2 (with M being Ca, Sr or Ba) [2935], or CaAlSiN 3 (abbreviated as CASN hereafter) [3640]. …”
Section: Introductionmentioning
confidence: 99%
“…The 537 nm peak in the GP70 and GP180 films is from the 4f 6 5d → 4f 7 transitions in Eu 2+ of the phosphor. 11,12 The GO−phosphor hybrid films show shoulder peaks at ∼500 nm (for GP70) and 510 nm (for GP180), which correspond to π−π* gap values of ∼2.56 and 2.43 eV, respectively. The origin of these emission peaks from the GO−phosphor hybrid films is discussed later.…”
Section: Resultsmentioning
confidence: 98%